O-H center dot center dot center dot O-bridged dimers linked via C-H center dot center dot center dot O and C-H center dot center dot center dot pi interactions in 4,6-di-O-benzyl-myo-inositol 1,3,5-orthoformate - Manoj, Kochunnoonny; Devaraj, Subramanian; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Acta Crystallographica Section C-Crystal Structure Communications, 2005)

Organocatalytic enantioselective vinylogous michael-aidoi cascade for the synthesis of spirocyclic compounds - Mondal, Santigopal; Mukherjee, Subrata; Yetra, Santhivardhana Reddy; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2017)
Enantioselective synthesis of pyrazolone-fused spirocyclohexenols by the secondary amine-catalyzed cascade reaction of alpha,beta-unsaturated aldehydes with alpha-arylidene pyrazolinones is reported. This formal [3 + 3] organocascade reaction proceeds through a vinylogous Michael-aldol sequence to furnish the spiroheterocycles with three stereocenters including an all-carbon quaternary center in good yields and selectivities. The catalytic generation of alpha,beta-unsaturated iminium ions from enals and tandem dienolate/enolate formation from pyrazolinones are the key for the success of this spiroannulation reaction.

Organocatalytic asymmetric cascade reaction of gamma-substituted deconjugated butenolides with o-formyl-beta-nitrostyrene - Deepake, Siddharth K.; Lanjewar, Atul B.; Thatikonda, Thanusha; Gonnade, Rajesh G.; Das, Utpal (ChemistrySelect, 2018)
An efficient chemo-, diastereo- and enantio-selective cascade synthesis of functionalized indanols bearing four contiguous stereogenic centres has been developed via the reaction of beta,gamma-butenolides with o-formyl-beta-nitrostyrenes in the presence of bi-functional hydrogen-bonding catalyst. Indanol derivatives containing gamma,gamma-disubstituted butenolides were obtained in good yields and with moderate to high enantioselectivities/diastereoselectivities.
Keywords: butenolides; Cascade reaction; Enantioselectivity; Indanol; organocatalysis

Organocatalysed one-pot three component synthesis of 3,3′-disubstituted oxindoles featuring an all-carbon quaternary center and [spiro 2H-pyran-3,4′-indoline] - Nichinde, Chandrakant B.; Patil, Baliram R.; Chaudhari, Suryakant S.; Mali, Bhupendra P.; Gonnade, Rajesh G.; Kinage, Anil K. (RSC Advances, 2023)
A simple and efficient methodology for the one-pot synthesis of 3,3 `-disubstituted oxindoles featuring an all-carbon quaternary center has been demonstrated through l-proline catalysed three-component reaction based on sequential Knoevenagel condensation/Michael addition and also one-pot synthesis of spiro[2H-pyran-3,4 `-indoline] through consecutive Knoevenagel condensation/Michael addition/reduction/cyclization reactions from readily available isatin derivatives, malononitrile, and ketones. The present methodology presents several advantages, including simple reaction set-up, short reaction times, and easy to work-up. Also, this strategy offers broad substrate scope with excellent yields and high atom economy, under mild reaction conditions.